2014
DOI: 10.1155/2014/309106
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception of Stroke: A Population-Based Survey in Uganda

Abstract: Purpose This study, designed to complement a large population survey on prevalence of stroke risk factors, assessed knowledge and perception of stroke and associated factors. Methods A population survey was conducted in urban Nansana and rural Busukuma, Wakiso district, central Uganda. Adult participants selected by multistage stratified sampling were interviewed about selected aspects of stroke knowledge and perception in a pretested structured questionnaire. Results There were 1616 participants (71.8% ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
76
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 21 publications
(34 reference statements)
11
76
4
2
Order By: Relevance
“…This was consistent with a study done in Khon Kaen, Thailand (Jirapornkul et al, ), which demonstrated a high level of stroke knowledge among people in suburban communities. However, our findings were not consistent with previous studies conducted in other countries (El Sherbiny, Abdel Ghaffar, & El‐Mously, ; Hickey et al, ; Nakibuuka et al, ; Zeng et al, ), which found a lack of stroke knowledge among the study populations. In this study, although older people with and without high risk of stroke were different in terms of comorbidities, the stroke‐preventive behaviors in both groups were at similarly high levels.…”
Section: Discussioncontrasting
confidence: 99%
“…This was consistent with a study done in Khon Kaen, Thailand (Jirapornkul et al, ), which demonstrated a high level of stroke knowledge among people in suburban communities. However, our findings were not consistent with previous studies conducted in other countries (El Sherbiny, Abdel Ghaffar, & El‐Mously, ; Hickey et al, ; Nakibuuka et al, ; Zeng et al, ), which found a lack of stroke knowledge among the study populations. In this study, although older people with and without high risk of stroke were different in terms of comorbidities, the stroke‐preventive behaviors in both groups were at similarly high levels.…”
Section: Discussioncontrasting
confidence: 99%
“…10 However, multiple studies in Uganda, Oman and India found that only a minority of their participants were able to identify the brain as the organ affected by stroke. 4,11,12 Post intervention, 98.1% )n=307( of participants pointed to the brain as the affected organ by stroke and 97.1% )n=304( explained the mechanism of stroke ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to previous studies. 4,10,11,12 After using the FAST approach in the educational session, )306( 97.8% of participants chose to go to the hospital immediately or would call an ambulance in case they recognized a stroke event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interruption of circulation leads to tissue death, as manifested by clinical signs and abnormalities on magnetic resonance imaging that are characteristic of ischemia (3) .According the extent and location of damage to brain tissue, stroke mayalso affect individuals' physical, mental,psychological and social functioning (4) .The main clinical manifestations areinability to move, aphasiaor dysphagia, vision alterations, mental changes, headache, numbness or tingling and dizziness or weakness . (5) More than half of all strokes are preventable, understanding of individuals their personal risk factor/ factors could lead to improve controlling of modifiable risk factors and reduced incidence of stroke . (6) Although the risk factors for a stroke are preventable and/or controllable, the public awareness of these risk factors is low.Smoking,hypertension, heart disease, high cholesterollevel ,obesity, sedentary lifestyle, diabetes, use of oral contraceptives,excess alcohol intake, and stress are the main modifiable risk factors for strokes .…”
Section: Introductionmentioning
confidence: 99%